Healthy Lifestyle and the Belgrade Marathon: Recreational Runnners or Fanatics? - Radenovic, Sandra S.; Mijatov, Nikola V. (Sociološki pregled, 2019)
The aim of the paper is to re-examine the concept of marathon as a sportsrecreational activity that presupposes a healthy lifestyle. Through the theoretical concept of escapism on the example of the Belgrade Marathon, the autobiographical book of a recreational marathon runner and autobiographical records of recreational runners, recreational participation in marathons is studied as a form of escapism from the problems of everyday life that ends up as a certain form of fanaticism. Fanaticism expressed in the imperative of success imposed through the obligation to finish the race changes the approach to a recreational activity whose goal is, among other things, to improve and nurture health. In the social context of neo-liberalism, this (self-)imposed imperative often leads in the direction of disrupting health for its own fulfillment.Keywords: marathon, health, escapism, recreationists, fanatics